(untitled) (Pedagogy of Higher and Secondary Education, 2009)
Independent work of students always played an important role in preparation of specialists, but especially it grew in postsovetskoe time, becoming basis of studies in Institute of higher. Reformation of the system of higher education puls before it new problems, and also search of ways of their overcoming.